2015
DOI: 10.1093/eurheartj/ehv023
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor temperature, blood pressure, and cardiovascular disease mortality among 23 000 individuals with diagnosed cardiovascular diseases from China

Abstract: IntroductionBlood pressure is a major cause of cardiovascular disease (CVD) and both may increase as outdoor temperatures fall. However, there are still limited data about seasonal variation in blood pressure and CVD mortality among patients with prior-CVD.MethodsWe analysed data on 23 000 individuals with prior-CVD who were recruited from 10 diverse regions into the China Kadoorie Biobank during 2004–8. After 7 years of follow-up, 1484 CVD deaths were recorded. Baseline survey data were used to assess seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(97 citation statements)
references
References 32 publications
4
88
0
5
Order By: Relevance
“…There is much evidence that seasonal meteorological variables influence blood pressure in both hypertensive and normotensive individuals, [33][34][35] and decreased outdoor temperature is in some way accompanied by increased intravascular systolic pressure. 36 Changes in AP may increase transmural arterial stress by transiently lowering tissue pressure with respect to blood pressure, creating a net expansive force. 37 The alteration in AP could also affect the partial pressure of oxygen and carbon dioxide in the circulation 38 and thus activate chemoreceptors and baroreceptors leading to elevated sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…There is much evidence that seasonal meteorological variables influence blood pressure in both hypertensive and normotensive individuals, [33][34][35] and decreased outdoor temperature is in some way accompanied by increased intravascular systolic pressure. 36 Changes in AP may increase transmural arterial stress by transiently lowering tissue pressure with respect to blood pressure, creating a net expansive force. 37 The alteration in AP could also affect the partial pressure of oxygen and carbon dioxide in the circulation 38 and thus activate chemoreceptors and baroreceptors leading to elevated sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The literature generally suggests that exposures to both high and low temperatures are associated with cardiovascular events in non-pregnant populations around the world (Basu, 2009; Bhaskaran et al, 2012; Ha et al, 2014; Honda et al, 2016; Phung et al, 2016; Sartini et al, 2016; Wang et al, 2016; Yang et al, 2015) with potentially higher sensitivity among Blacks women, those with lower socioeconomic status, the elderly, and young children (Basu, 2009); but data among pregnant women are currently lacking. One large international multicenter case-control study among reproductive age women ages 15 to 49 showed that each 5°C decrease in monthly average temperature was associated with a 7% and 12% increase in hospital admission rates for stroke and acute myocardial infarction, respectively; and these effects were more prominent within one month of exposure (Chang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have linked extreme ambient temperatures with acute cardiovascular risk in the general population as well as in susceptible subgroups including those with lower socioeconomic status, the elderly, and those with other comorbid conditions (Medina-Ramon and Schwartz, 2007; Wang et al, 2016; Yang et al, 2015). A role for temperature in the pathogenesis of cardiovascular risks is plausible given the oxidative stress and systemic inflammation induced shortly after exposure (Cai et al, 2016; Cheng et al, 2015; Halonen et al, 2010; Hong et al, 2012; Quindry et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that winter morning surge in BP would be associated with increased cardiovascular events during winter. 23,24 We should pay attention to the onset of cardiovascular events triggered by winter morning surge in BP, especially in elderly hypertensive patients who own their homes.…”
Section: Discussionmentioning
confidence: 99%